Human PMNs exhibit greater engulfment, NETosis, and enhanced migration when incubated with nontypeable Haemophilus influenzae newly released from a biofilm - Wilbanks, Kathryn Q.; Flesher, Joshua; Goodman, Steven D.; Bakaletz, Lauren O. (Frontiers in Microbiology, 2025)
Biofilm-resident bacteria exhibit diverse mechanisms to evade eradication, including the highly protective self-produced matrix in which they are embedded. Thus, releasing bacteria from biofilm residence affords antibiotics and immune effectors greater access. We developed a monoclonal antibody directed against an essential biofilm matrix protein that induces rapid collapse of the biofilm matrix with release of bacteria that are in a transient but highly vulnerable phenotype. Bacteria that are newly released (“NRel”) due to this monoclonal are significantly more sensitive to antibiotic-, antimicrobial peptide- or human PMN-mediated killing in vitro and are rapidly eradicated in four animal models without adjunct antibiotic treatment, the speed of which highlights the role of innate immune effectors. Here, we characterized the reactivity of human PMNs to three distinct bacterial populations derived from three clinical isolates of the predominant respiratory tract pathogen nontypeable Haemophilus influenzae (NTHI). Via timelapse microscopy and flow cytometry, PMN engulfment, NETosis (e.g., programmed neutrophil cell death accompanied by release of web-like condensed DNA with associated antimicrobial proteins), and migratory activity were assessed when PMNs were incubated with NTHI that were dual-fluorescently labeled with green-fluorescent FM 1–43 and pH-sensitive red-fluorescent pHrodo™ Red, SE, which fluoresces in acidic environments such as within a phagolysosome. Relative concentrations of endotoxin and DNA, as well as cytokines/chemokines potentially responsible for observed PMN activities were also assessed. PMN-mediated engulfment, NETosis, and migratory activity were all greatest when incubated with NTHI NRel compared to both NTHI that had been grown planktonically in rich medium or to NTHI that were present in the culture medium that overlayed the biofilm. Whereas neither NTHI endotoxin nor DNA played a role in the observed relative activities, PMNs incubated with NTHI NRel released significantly more IL-8 which likely served to enhance the migration of additional PMNs. These data contribute to our understanding of mechanisms anticipated to be operational in the DNABII protein-targeted monoclonal antibody-based treatment regimen we developed to facilitate host-mediated contribution to biofilm eradication after induced release of formerly biofilm-resident bacteria into the highly vulnerable NRel state.